2016
DOI: 10.1590/1414-462x201600020238
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ reports of occupational exposures to potentially infectious biological material in a Brazilian School of Dentistry

Abstract: Introduction: Occupational exposures to contaminated biological material in dental teaching settings can place students at higher risk of bloodborne infections. Methods: This cross sectional study was conducted using a self-administered questionnaire culturally adapted to Portuguese language, Brazil. In total, 173 undergraduate dental students agreed to participate in the study, answered the questionnaire, and filled in the details about their own occupational exposures. The association of these factors was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
(20 reference statements)
0
6
1
15
Order By: Relevance
“…The high index of studies carried out with academics shows the commitment to the training of future professionals, seeking to enable them to apply the guidelines in biosafety in order to promote a safe clinical environment. Several studies [3,6,7,[11][12][13][14][15][16][17][18] point to the need to develop teaching strategies that cover not only theoretical knowledge, but also daily practice.…”
Section: Year Of Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high index of studies carried out with academics shows the commitment to the training of future professionals, seeking to enable them to apply the guidelines in biosafety in order to promote a safe clinical environment. Several studies [3,6,7,[11][12][13][14][15][16][17][18] point to the need to develop teaching strategies that cover not only theoretical knowledge, but also daily practice.…”
Section: Year Of Publicationmentioning
confidence: 99%
“…The authors mentioned that an institution that had a biosafety committee presented better results regarding the use of PPE and accident notification. Pinelli et al [17] evaluated the prevalence of occupational accidents and verified their occurrence in 40% of the study participants. In addition, they noted that 52% of accidents were not properly reported.…”
Section: Year Of Publicationmentioning
confidence: 99%
“…Studies have shown the importance of complying with biosafety protocols and controlling cross‐contamination, especially in dentistry, where the work environment is susceptible to contamination with pathogens . Infection control in the dental practice involves special care for tubes containing CR because this material may become contaminated during handling, potentially causing cross‐contamination .…”
Section: Identification Of Microbial Species and The Numbers Of Colonmentioning
confidence: 99%
“…Even at dental schools, dental students did not comply with infection control practices very well [13], [31], [34], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51]. …”
Section: Introductionmentioning
confidence: 99%